Comparative ablation rate from a Er : YAG laser on enamel and dentin of primary and permanent teeth - Lizarelli, R. de F. Z.; Moriyama, L. T.; Jorge, J. R. P.; Bagnato, V S (Springer, 2006)
This study was conducted to analyze the ablation rate and micromorphological aspects of microcavities in enamel and dentin of primary and permanent teeth using a Er:YAG laser system. Micromorphological evaluation has been performed in terms of permanent teeth; however, little information about Er: YAG laser interaction with primary teeth can be found in the literature. Because children have been the most beneficiary patients with laser therapy in our offices, it is extremely necessary to compare the effects of this kind of laser system on the enamel and dentin of permanent and primary teeth. In this study, we used eleven intact primary anterior exfoliated teeth and six extracted permanent molar teeth. We used a commercial laser system: a Er: YAG Twin Light laser system (Fotona Medical Lasers, Slovenia) at 2940 nm, changing average energy levels per pulse ( 100, 200, 300, and 400 mJ) producing 48 microcavities in enamel and dentin of primary and permanent teeth. Primary teeth are more easily ablated than are permanent teeth, when related to enamel or dentin. However, while this laser system is capable of slowly revealing the enamel's microstructure, in dentin only the lowest laser energies permit this kind of observation, more easily decomposing the original tissue aspect, when related to primary or permanent teeth. Statistically, the only different factor at the 5% level was an energy per pulse of 400 mJ, confirming the results found in SEM. Our results showed that dentin in both primary and permanent teeth is less resistant to Er: YAG laser ablation; this fact is easily observed under SEM observation and through the ablation rate evaluation.